PENGEMBANGAN APLIKASI HUMAN RESOURCE INFORMATION SYSTEM (HRIS) BERBASIS WEB DENGAN METODE PROTOTYPE - Nico Marbun; Syamsul Ma’arif; Tsaniyatus Solikhah (Journal of Research and Publication Innovation, 2025)
In the era of globalization, human resource management (HRM) has become one of the main challenges for companies. PT. Bemfood Eka makmur Nusjaya faces difficulties in managing employee data, leave requests, and payroll, which are still conducted manually, resulting in low work efficiency and vulnerability to errors. This manual process also consumes a significant amount of time and resources, ultimately affecting the company's productivity. This study aims to design and implement a web-based Human Resource Information System (HRIS) using the prototype method. This methodology allows for iterative development with direct feedback from users, ensuring the system aligns with the company's operational needs. The research results show that the designed HRIS application can improve HR management efficiency through integrated features for managing leave, payroll, and employee data. Furthermore, the implementation of a web-based system enhances accessibility for users in various locations and increases the accuracy of recorded data. This application is expected to be an innovative solution to support more effective and efficient HR management.